INTERSTITIAL LUNG DISEASE ASSOCIATED WITH SYSTEMIC SCLEROSIS - L. P. Ananyeva (Научно-практическая ревматология, 2017)
The basis for the pathogenesis of systemic sclerosis (SS) is immune disorders that initiate inflammation, as well as vasculopathy with obvious microcirculatory disturbances, and generalized fibrosis. In SS, lung injury is due to an arterial lesion and/or a fibrotic process in the lung parenchyma and occurs as two major syndromes that are rarely concurrent in one patient; these are pulmonary arterial hypertension and interstitial lung disease (ILD). In SS, lung injury negatively affects the prognosis and ranks first among the causes of death. The review focuses on ILD, the most common injury of the respiratory tract in SS, which is detectable in 80% of patients, as evidenced by multislice spiral computed tomography (MSCT) of the chest. The histological manifestations are similar to those of idiopathic ILDs, but the histological type does not determine the prognosis. The course of ILD in SS is relatively benign, often subclinical. A severe progressive lesion develops only in 10–15% of cases. Clinically significant changes in the lung parenchyma develop early, within the first 3–5 years of the disease. Pulmonary functional tests show that relatively preserved and stable forced vital capacity is long recorded in the majority of patients, but the diffusing capacity of the lung is reduced in 70–80% of the patients. The values of pulmonary tests during the first examination are of prognostic value; the lower than normal they are, the worse the prognosis. Chest MSCT should be carried out in all patients with newly diagnosed SS, as the quantitative (prevalence) and qualitative (frosted glass, honeycomb lung) indicators affect the determination of therapy policy. ILD treatment is performed only in patients with obvious signs of progression, which are determined from the time course of changes in the decrease of values of pulmonary functional tests. Immunosuppressants, cyclophosphamide being the drug of choice, are used to treat ILD; biological agents, tocilizumab in particular, are currently being tested.